PRECARITY, AGENCY, AND UNSUSTAINABILITY: THE MOBILITY OF YOUNG ADULT TOURISM WORKERS IN BANFF NATIONAL PARK, CANADA - Smith, Angèle (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2021)
This article focuses on young adults who travel to work and live in the Rocky Mountain resort destination of Banff National Park in western Canada. This is usually an early work experience in the lives of these young workers, often their first. I discuss the patterns and the impact of the work mobility of young adult tourism workers using three different frames of understanding: (a) the precarious employment associated with the tourism industry itself; (b) the specific place and community of Banff and how it shapes particular conditions of precarity and agency within the tourism industry and for young tourism workers’ experiences; and (c) the young adult tourism workers themselves — their motives for work and travel, their experiences of work, and their agency in navigating the tourism industry in Banff. Using these three frames, I examine the impact of precarity and agency on the transfer of work knowledge, on the sustainability of the tourism industry work and the community, and on the young adult tourism workers’ future work experiences. It is critical to examine work precarity, worker agency, and job and community sustainability in order to understand more fully the experiences of mobility of young adult tourism workers, and their early work experiences. This is all the more important as, in a climate of economic change and restructuring, young adult workers are becoming central to the consideration of employment policy issues.